Uranium in vegetable foodstuffs: should residents near the Cunha Baixa uranium mine site (Central Northern Portugal) be concerned ? - Neves, M.O. (2012)
Large uranium accumulations in vegetable foodstuffs may present risks of human health if they are consumed. The objective of this study was to evaluate the uranium concentrations in different vegetable foodstuffs and grown in agricultural soils, which are then consumed by the residents of the village of Cunha Baixa (Portugal),—located in an former uranium mining area. This study was conducted to address concerns expressed by the local farmers as well as to provide data for uranium-related health risk assessments for the area. Soils, irrigation water and edible tissues of lettuce, potato, green bean, carrot, cabbage, apple and maize (Latuca sativa L., Solanum tuberosum L., Phaseolus vulgaris L., Daucus carota L., Brassica oleracea L., Malus domestica Borkh, Zea mays L., respectively) were sampled and uranium determined. High uranium concentrations were found in some soils (Utotal[50 mg/kg), in irrigation waters (218 to 1,035 lg/l) and in some vegetable foodstuffs (up to 234, 110, 30, 26, 22, 16 and 1.6 lg/kg fresh weight for lettuce, potato with peel, green bean pods, cabbage, corn, carrot and apple, respectively). However, the results of the toxicity hazard analysis were reassuring the estimated level of uranium exposure through the ingestion of these vegetable foodstuffs was low, suggesting no chemical health risk (hazard quotient \1) to this uranium exposure pathway for a local residents during their lifetime, even for the most sensitive part of the population (child).